Improving same-day access in primary care: Optimal reconfiguration of appointment system setups. (September 2018) - Schacht, Matthias
Abstract: A concept for the optimal configuration and capacity allocation for appointment systems in primary care is presented. It is designed to provide decision-support for primary care clinics to cope with seasonal variations in patient load in order to assure a high accessibility to health care services. The central aspect of the concept is a stochastic MILP for the determination of an appointment scheduling setup configuration, which is defined by the allocation of walk-in and pre-scheduled appointment blocks in combination with the allocation of daily service times. The tactical decision is the efficient allocation of capacity for walk-ins and pre-scheduled patients, where it has to be assured that urgent patients have sufficient access to health care services. In this paper, it is analyzed to which extent reconfigurations in the appointment system setup and incorporation of uncertainty with respect to patient load is beneficial. The main contribution is a concept determining efficient appointment systems to cope with stochastic and seasonal patient load by reconfiguring the appointment system throughout the year. A case study provides managerial insight for varying patient settings, suggesting that even with a high share of urgent patients there is a significant benefit of reconfiguring the appointment system throughout the year.